Lower limb movement variability during rugby union place kicking - Ford, S.; Sayers, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Place kicking accuracy has a significant impact rugby match outcomes. This project investigated the variability of the kicking leg kinematics and the consistency on the stance and kicking foot positions at ball contact in a group of seven highly proficiency kickers. Kinematic data were collected using a high speed motion capture system (500 Hz) during six simulated attempts on goal. Movement variability was assessed using Normalised Root Mean Square of the swing leg pelvis, hip and knee kinematics, and the standard deviation of the stance foot at opposite plant and kicking foot at ball contact (BC). Results suggest a strong relationship between stance foot placement, swing leg movement variability and the orientation of the kicking foot at BC. This pilot study highlighted the importance of movement variability in determining consistent foot placement at BC in place kicking.